Color index of transformer oil: A low-cost measurement approach using ultraviolet-blue laser - Hadi M.H.H.; Ker P.J.; Lee H.J.; Leong Y.S.; Hannan M.A.; Jamaludin M.Z.; Mahdi M.A. (MDPI, 2023)
Costs; Linear regression; Mean square error; Oil filled transformers; Power transformers; American society for testing and material d1500; American society for testing and materials; Blue lasers; Blue wavelength; Color index; Condition; Low-cost measurements; Single wavelength; Transformer oil samples; Ultraviolet-blue wavelength; Color; human; laser; power supply; Electric Power Supplies; Humans; Lasers